Tradisi Pembacaan Surah Yasin Malam Nisfu Sya’ban di Pontianak Timur, Kalimantan Barat: Analisis Sosiologi Pengetahuan - Ihsan Nurmansyah; Putri Rizqy, Fina Hilmina (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2024)
This article discusses the tradition of reading Surah Yasin on the night of Nisfu Sya'ban at Surau al-Ikhlas, East Pontianak, West Kalimantan. In its implementation, Surah Yasin is recited three times, then continued with the recitation of the Apostle's prayer and a serving of yellow pulut on top of which is placed grilled chicken. Therefore, to find out the meaning of this tradition is to use Karl Mannheim's theory of the sociology of knowledge. The data sources were obtained from interviews with the management or chief executive and the Imam who led the reading as well as direct observations in the field. The results of this research are: 1) the objective meaning from the perspective of the Surau al-Ikhlas congregation, namely preserving the traditions of previous elders as a form of obedience to the cleric named KH. Yunus Mohan found his handwritten notes which were used as a reference. 2) the expressive meaning in the view of the Surau al-Ikhlas congregation, namely as a cure for all diseases, asking for determination of faith, asking for long life and lots of halal sustenance. 3) the documentary meaning of the tradition of reading Surah Yasin on the night of Nisfu Sya'ban is the formation of a habit as a forum for unity and brotherhood of the Surau al-Ikhlas congregation. Keywords: Living Qur’an, Surah Yasin, Nisfu Sya'ban, Sociology of Knowledge